Sufism in classical Kurdish poetry: (Poems on Hariri as a model) - Rabeea Ismael Khalid ZEBARI; Bafreen Rasheed Huseein (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Sufism is considered one of the most important subjects of world literature in general and Kurdish literature in particular. Sufism is used within the literature as a means of purifying the heart and mind. This becomes a message that the author directs to the reader. In this message, the author tries to purify his heart and mind toward his God through this message. This conveys to the reader what is on his mind directly. There is no doubt that Sufism is reflected in Kurdish poetry in general and in classical poetry in particular. Degrees of Sufism are also seen as a major theme in Ali’s poems; therefore, we thought it necessary to select this theme and identify the reflection of Sufism in the poems of Ali Hariri classic poems.